Interference in Antiphospholipid Antibody Assays - Lakos, Gabriella (Seminars in Thrombosis and Hemostasis, 2012)
Antiphospholipid antibodies (aPL) are detected with two types of laboratory tests: first, antigen-specific immunoassays for the determination of antibodies against cardiolipin, β2-glycoprotein I and other phospholipids, and phospholipid−protein complexes; second, functional (coagulation) assays for the detection of lupus anticoagulants. Both aPL immunoassays and coagulation assays are prone to interferences, and clinicians need to be aware of the limitations of these assays. Interference is a clinically significant bias in the measured analyte concentration due to the effect of another component or property of the sample. Besides immune-mediated interferences (such as heterophile or human anti-animal antibodies, rheumatoid factor, high immunoglobulin levels, or factor inhibitors), aPL assays are uniquely affected by anticoagulants and the presence of residual platelets in test plasma. Interferences are usually analyte- and assay-specific and may go unrecognized in routine laboratory practice. Despite advances in our knowledge on the mechanisms of interferences in aPL assays, it is unlikely that total elimination will be possible.
Keywords: antiphospholipid immunoassays; lupus anticoagulant; heterophile antibodies; rheumatoid factor; anticoagulants